Integration at the workplace studies within multinational pharmaceutical factories in Hungary - Kozák, Anita (Applied Studies in Agribusiness and Commerce, 2012)
The primary objective of this essay is to assign a gap in Human Recourse Management literature. Many studies and resources are known about hiring and maintaining people and their loyalty to organizations. Work socialization is the first step to keeping people; however, most of the literature on integration at the workplace focuses primarily on organizational commitment and not on the individuals. Various perspectives of work socialization have been discussed including socialization stages, guidance and carrier development. This essay focuses on the approach of Human Resource Management, but the scope is expanded to the individual as well. In this paper, the reasoning, the methods and the questions of my future doctoral research on integration at the workplace are analysed. First, the issue is discussed from the perspective of social changes in Hungary. The next part of this essay illustrates varying definitions from the literature, providing then my own view of how to explain the integration process in the workplace and through which what I would like to focus my research. This article also aims to show possible methods (in-depth interviews with Human Resource Managers and document analysis) for examining the topic at multinational pharmaceutical factories in Hungary, while highlighting the most important questions for which my research aims to find answers.